Författarens välklädda lik: En familjeförsörjares död på könskampens slagfält i August Strindbergs Giftas - Cavallin , Anna (Tidskrift för litteraturvetenskap, 2013)
The Well-Dressed Corpse of the Author. The Death of a Family-Provider on the Frontlines of the Sex-War in August Strindberg’s Giftas (Getting Married) This text examines how the short story, ”Familjeförsörjaren” (”The Family Provider”) – part of the 1886 collection, Giftas II – represents and problematises masculinity and the role of the author as a professional in the late 19th century. Strindberg wrote his two Giftas-collections at a time in which masculinities and femininities where vividly debated in Sweden in journals, newspapers and in fiction – when the roles and functions of men and women in society, in marriage and the home, and traditional gender-based tasks for men and women were questioned. With the emergence of the ”New Woman”, both as a reality, in the shape of independent women, and as a literary figure, the function of the bread-winning husband, the pater familias, was questioned. Moreover, with the emergence of a great number of women as authors in the 1880’s, the art and profession of fiction-writing came to be perceived as feminine. The late 1880’s witnessed the emergence of a movement on behalf of male authors who wished to reclaim fiction-writing as a male-coded profession. In Giftas, and in ”Familjeförsörjaren” specifically, this act of reclaiming is made visible through Strindberg’s representation of male authors in contrast with women who write. These women are depicted as imitating others, copying for example Sappho and Mme de Staël, while the writing bread-winner in ”Familjeförsörjaren” is the original, male genius, creating under great strains. On the other hand, the masculinity of this bread-winning male author is ambivalent: he is both hyper-sensitive (a characteristic which likens him to the androgynous figure of the dandy), and creates an orderly, well-written text. The story ends in the death of the author and the bread-winner but nothing has actually changed in the battle between men and women – rather the seriousness of the struggle is accentuated now that there are dead bodies to count.